2018
DOI: 10.29298/rmcf.v6i29.215
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de Arceuthobium vaginatum (Willd.) Presl. subsp. vaginatum en Pinus hartwegii Lindl. en Colima

Abstract: árboles en un rodal natural con presencia de muérdago enano: nueve sanos y nueve enfermos; con edades entre 30 y 40 años a los cuales se les realizaron análisis troncales para reconstruir su historial de crecimiento. Se consideró el grado de infección 6, con base en el sistema de clasificación de Hawksworth. Se probaron las ecuaciones de Shumacher y Chapman-Richards a fin de seleccionar el modelo más adecuado para la descripción del fenómeno. El modelo de Shumacher presentó mejores ajustes en la predicción del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
3
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 4 publications
2
3
0
2
Order By: Relevance
“…These reduced height growths for infected trees were similar (22%) to that reported by Martínez Salvador et al (2015) for severely infected, 30-40 year old Pinus hartwegii. These reduced height growths for infected trees were similar (22%) to that reported by Martínez Salvador et al (2015) for severely infected, 30-40 year old Pinus hartwegii.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…These reduced height growths for infected trees were similar (22%) to that reported by Martínez Salvador et al (2015) for severely infected, 30-40 year old Pinus hartwegii. These reduced height growths for infected trees were similar (22%) to that reported by Martínez Salvador et al (2015) for severely infected, 30-40 year old Pinus hartwegii.…”
Section: Discussionsupporting
confidence: 85%
“…year period (51-60 years) was as high as 21%. These reduced height growths for infected trees were similar (22%) to that reported by Martínez Salvador et al (2015) for severely infected, 30-40 year old Pinus hartwegii. But, the reductions in height growth were much lower than that reported by other investigators who found reductions in height growth of severely infected trees as high as 65% (Andrade Escobar & Cibrián, 1980;Mathiasen et al, 1990;Uribe, 1985).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations